Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41467-018-06498-2
|View full text |Cite
|
Sign up to set email alerts
|

ATRX, DAXX or MEN1 mutant pancreatic neuroendocrine tumors are a distinct alpha-cell signature subgroup

Abstract: The commonly mutated genes in pancreatic neuroendocrine tumors (PanNETs) are ATRX, DAXX, and MEN1. We genotyped 64 PanNETs and found 58% carry ATRX, DAXX, and MEN1 mutations (A-D-M mutant PanNETs) and this correlates with a worse clinical outcome than tumors carrying the wild-type alleles of all three genes (A-D-M WT PanNETs). We performed RNA sequencing and DNA-methylation analysis to reveal two distinct subgroups with one consisting entirely of A-D-M mutant PanNETs. Two genes differentiating A-D-M mutant fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 40 publications
(66 reference statements)
19
156
0
Order By: Relevance
“…Since reliable cytologic determination of PDX1 is critical to determine the prognostic subgroups as described in Cejas et al, cytologic PDX1 interpretation should be performed with caution, but concerning prognostic value, this study was too limited in size to draw strong conclusions. The high percentage of ARX positive non‐functional PanNETs (17/18) compared to 50% to 60% in recent studies, might be caused by selection bias and reflect more aggressive/faster growing tumors that warranted biopsy.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Since reliable cytologic determination of PDX1 is critical to determine the prognostic subgroups as described in Cejas et al, cytologic PDX1 interpretation should be performed with caution, but concerning prognostic value, this study was too limited in size to draw strong conclusions. The high percentage of ARX positive non‐functional PanNETs (17/18) compared to 50% to 60% in recent studies, might be caused by selection bias and reflect more aggressive/faster growing tumors that warranted biopsy.…”
Section: Discussionmentioning
confidence: 79%
“…PDX1 or double positive expression on the other hand identified a more indolent group, in which only few tumors relapsed . Similarly, Chan et al showed, using RNA sequencing and whole genome methylation, that the ARX positive, PDX1 negative subgroup was often associated with somatic mutations in ATRX , DAXX , or MEN1 and a worse prognosis …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Samples used for each assay and their characteristics are shown in Figure 1a, further details are depicted in Supplementary Table 1. The cohort includes tumors of grades NET G1 (27) and NET G2 (25) NET G3 (4), and NEC (3), 45 samples were primary PanNENs and 14 were metastases (8 liver, 6 lymph nodes). As healthy control we used matched adjacent healthy (24) or distant healthy tissue (27) or blood (4) from the same patient.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Comparison of PanNEN MEN1/DAXX/ATRX-mutated and -wildtype subgroups by whole transcriptome profiling revealed a gene expression signature similar to α-cells of the Islets of Langerhans only in the mutant group 27 . The specific signature showed a strong expression of the well-established α-cell-specific transcription factor ARX.…”
Section: Introductionmentioning
confidence: 98%